ANALISIS IMPLEMENTASI SISTEM SAP R/3 PADA PT XYZ - , Elvi Yustika; , Dr. Eko Suwardi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Enterprise Resource Planning (ERP) is an integrated information system technology is used by companies in improving company performance and can quickly describe condition of the company. One of the ERP systems is SAP. Research conducted by the author to know the process of implementing SAP R/3 on PT. XYZ where used Accelerate SAP (ASAP) as implementation methodology, which is a standard SAP and connect it with the factors that influence the process and result of implementation. Implementation of SAP R/3 is a strategic decision by management of PT.XYZ after the merger condition of three companies and should be done in a short period with a tight project schedule. ERP Implementation is not easy and has great potential for failure. Many studies claim that the majority of ERP implementations have failed because many factors influence, for example a study conducted by gargeya and Brady (2005). Result from this research describe that the implementation process is successfully carried out in accordance with planned targets, so the company operations can run smoothly and provide convenience to users and provide benefits to the company overall.